RESPON PEMBERIAN PAKAN KOMERSIAL DENGAN DOSIS BERBEDA TERHADAP PERTUMBUHAN BERAT MUTLAK IKAN GURAMI (Osphronemus gourmy) UKURAN 2-3 CM DI BAK BAK PERCOBAAN - Onivia Faradila Nur Qoirin; Muhajir; Sri Oetami Madyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The gourami fish (Osphronemus gouramy) is a type of freshwater fish that is highly sought after by the public because it has the advantage of being easy to breed naturally, can survive in stagnant water, and has high economic value. Gourami fish measuring 2-3 cm have a mortality rate of 50-70%, one of the causes being feed quality. Gourami fish measuring 2-3 cm can consume natural and commercial feed. Commercial feed has many advantages, including complete and balanced nutritional composition and consistent availability throughout the year. One important element of feed management is feed dosage. Overfeeding can pollute the aquatic environment, while underfeeding can cause malnutrition, thereby inhibiting growth. This study used an experimental method with a completely randomized design (CRD) consisting of 5 treatments and 5 replicates. The treatments in this study were the provision of commercial feed at different dosages. Treatment A: 2% of the biomass weight of the test animals; Treatment B: 5% of the biomass weight of the test animals; Treatment C: 8% of the biomass weight of the test animals; Treatment D: 11% of the biomass weight of the test animals; and Treatment E: 14% of the biomass weight of the test animals. Test animals used were 2-3 cm long gurami fish with an average weight of 0.2 g/fish, stocking density of 2 fish/L, and the experimental medium used was fresh water with a volume of 3 L/container. The results showed that treatment C gave the best results for the absolute weight growth of 2-3 cm long gurami fish, which was 0.42 g/fish. Water quality data obtained showed that the water temperature ranged from 26.1 to 27.9°C, the acidity level ranged from 7.0 to 7.9, and the dissolved oxygen ranged from 5.29 to 5.67 ppm.